Evaluation of the Labor Inclusion of People with Auditory Disability Assisted with Technology - Callupe Pérez, Rocío (2023)
Fostering labor inclusion of workers with disabilities allows them to achieve both functional and economic autonomy. To achieve this inclusion, workspaces must be adapted according to the type of business and the worker’s needs. In the case of food production companies, these spaces are known as “inclusive kitchen models”. Therefore, this research aims to evaluate labor inclusion of people with auditory disability (PAD) while using the Willy wearable smartwatch. This wearable was used to transmit instructions through symbolic communication to PAD workers. This case study was performed at Grupo Empresarial WillCorp Perú SAC. The evaluation methodology is based on two techniques, one observational with temporal variables, and the other is a survey based on the Mckinsey Inclusion Assessment Practices model to measure the importance of their PAD workers’ perceptions of improving workplace inclusion using assistive technology (AT). It was observed that the group that used the wearable had an improvement in the activity response time in comparison with the control group, with an average of 9.4 seconds; and a significant decrease in the group response time was found, which generated greater satisfaction (p < 0.05). Furthermore, the perception of labor inclusion by workers was positive regarding the use of AT to improve equity in communication between them, according to the results of the survey for each of the variables and practices selected from the evaluation practices model. Finally, from a quantitative perspective, the Mckinsey inclusion criteria presented moderate alignment (90 %).